Neurosurgical Management in Left Ventricular Assist Device (LVAD) Patients With Intracerebral Hemorrhage (ICH). (1st September 2019) - Mueller, Kyle; D'Antuono, Matthew R; Zhao, David; Mai, Jeffrey C; Aulisi, Edward F; Felbaum, Daniel; Hockstein, Michael; Armonda, Rocco
Abstract: INTRODUCTION: Intracranial hemorrhage (ICH) is one of the most dangerous events in patients with a left ventricular assist device (LVAD) and poses a significant management challenge for neurosurgeons. These patients require anticoagulation to prevent pump thrombosis; however, the occurrence of ICH mandates stoppage of anticoagulation to prevent further hemorrhage. Given this management challenge, our aim was to assess outcomes in LVAD patients who suffered an ICH. METHODS: A retrospective review of a large volume LVAD center over a 2-yr period (January 2017-January 2019) was performed. LVAD patients with ICH requiring a neurosurgical consultation were identified. Hemorrhage type along with interventions and patient outcomes were recorded. RESULTS: We identified 27 LVAD patients with ICH that received a neurosurgical consultation. The average INR at the time of ICH was 2.7 (1.0-8.8). Hemorrhage types seen were lobar (10/27, 37%), subarachnoid hemorrhage (SAH) (5/27, 19%), SDH (4/27, 15%), cerebellar ICH (3/27, 11%), multiple ICH (3/27, 11%), and hemorrhagic conversion (2/27, 7%). The overall mortality rate was 48.2% (13/27), with the highest mortality being in those patients who had multiple ICH at the time of presentation (3/3, 100%). The majority of patients with ICH (85.2%) were nonoperative. Lobar IPH was >3 cm in 80% (8/10) of these, and 6/8 (75%) ultimately died. In total, 11% (3/27) received surgical intervention. Of these, 67% ultimately withdrew care. In total, 77% (10/13) of patients died as a result of the ICH. In total, 80% of patients with SAH were ultimately discharged home. CONCLUSION: Patients with an LVAD and lobar IPH >3 cm or multiple ICH had a universally poor prognosis despite any intervention. ICH type and size in LVAD patients may predict patient outcomes and could be used to triage operative vs nonoperative candidates.